6+2x=-6x-90

Simple and best practice solution for 6+2x=-6x-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x=-6x-90 equation:


Simplifying
6 + 2x = -6x + -90

Reorder the terms:
6 + 2x = -90 + -6x

Solving
6 + 2x = -90 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
6 + 2x + 6x = -90 + -6x + 6x

Combine like terms: 2x + 6x = 8x
6 + 8x = -90 + -6x + 6x

Combine like terms: -6x + 6x = 0
6 + 8x = -90 + 0
6 + 8x = -90

Add '-6' to each side of the equation.
6 + -6 + 8x = -90 + -6

Combine like terms: 6 + -6 = 0
0 + 8x = -90 + -6
8x = -90 + -6

Combine like terms: -90 + -6 = -96
8x = -96

Divide each side by '8'.
x = -12

Simplifying
x = -12

See similar equations:

| 5x-10+1x+3=8 | | 13+5r=2(5+2r) | | 4(7x+4)-9=28x+7 | | x^3+5x+3x+15=0 | | 4a+2=3a+7 | | 0=-4x^2-16x+20 | | 201(6+6)= | | 2-4h=6-6h | | -50+1.0x=300 | | 4x-3=-103-6x | | Y=-4x-16x+20 | | 2x+5-8w=7-4w | | 3m+3-m=3(m+1) | | -1v+5+4v=1+5v+3 | | (2i+3)(7i+6)= | | 9x+6(3x-4)=12-9x | | 3a-11=4(a+1)+13a+3 | | 2g-8+3g=7 | | .17(x+29)=86 | | 2x-6=5x+27 | | 2y^2-7y-10=0 | | 4x-2(.50-1)=14 | | 101(87+13)= | | y^3+729= | | 4x-2(x-2)=-7+4x+5 | | 9x-12=84 | | 4(2x-3)=30 | | 15-12z=21 | | .17(x-29)=86 | | 2x=1-5 | | 7(x+2)=5(x+14) | | p-4=-1+2P |

Equations solver categories